A Study of Termite Damage in Relation to Chemical Composition of Bamboos - Dhawan, Seema; Mishra, S. C.; Dhawan, Salil (Indian Forester, 2007)
Nutrition in insects is primarily concerned with the chemical substances present in the food. Some wood species are known to possess inherent quality of comparative termite resistance, which is attributed to its physical and chemical properties. Bamboos are susceptible to termite attack. Chemical composition of bamboo influences the consumption and assimilation of food by termites. The knowledge of chemical composition of bamboos is essential for the study of possible causes of termite attack. In the present research work, three important bamboo species B. polymorpha, B. aundinacea and D. strictus were studied for their chemical composition in relation to termite attack. The results indicate that the quantity of oligosaccharides, and polysaccharides does not seem to play a significant role in termite resistance quality. Nitrogen content in bamboo is directly related with termite damage. The quantity of lignin, ash content and silica content present in bamboo influence termite damage and play a significant role in termite resistance property of bamboo.